Evaluation of the themes chosen for the dissertation of the Integrated Master’s Degree of the Children’s Oral Health and Prevention Service, at IUCS-CESPU - Azevedo, Mariana; Ferreira, Maria João; Cantante, Juliana; Oliveira, Ana Catarina; Lobo, Ana Paula; Sousa-Santos, Primavera; Vale, Teresa (Scientific Letters, 2024)
The Children’s Oral Health and Prevention Service at IUCS-CESPU comprises three areas – Pediatric Dentistry, Orthodontics and Preventive Dentistry –, which, in the final years of the Integrated Master’s Degree in Dental Medicine, are taught within the scope of a single subject, the Pediatric Dentistry Clinic. Many of the topics covered here have stagnated due to a lack of knowledge, making it essential to recognize which areas are less popular, to captivate the interest of the students and fill these gaps. This study aimed to assess which topics in this service have more interest from dental students for their dissertations over the past eleven years. To do this, we collected all the dissertations between 2013-2023 in the Scientific Repository from the abovementioned service. Our study revealed a dominance of Orthodontics, followed by Preventive Dentistry and Psychology and Behavior Control. On the other hand, Pulpar Therapy, Diagnosis and Growth and Development are areas of little focus to students. We concluded that Orthodontics has always been the area of choice, while Preventive Dentistry, ranking second, has been in constant decline since 2015, as have Cariology and Conservative Treatments. Evaluating these choices allows us to better target teaching and meet the needs of the population.